2013
DOI: 10.1104/pp.113.230136
|View full text |Cite
|
Sign up to set email alerts
|

Sterol-Dependent Induction of Plant Defense Responses by a Microbe-Associated Molecular Pattern from Trichoderma viride      

Abstract: Plant-microbe interactions involve numerous regulatory systems essential for plant defense against pathogens. An ethylene-inducing xylanase (Eix) of Trichoderma viride is a potent elicitor of plant defense responses in specific cultivars of tobacco (Nicotiana tabacum) and tomato (Solanum lycopersicum). We demonstrate that tomato cyclopropyl isomerase (SlCPI), an enzyme involved in sterol biosynthesis, interacts with the LeEix2 receptor. Moreover, we examined the role of SlCPI in signaling during the LeEix/Eix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Because we determined that CK enhances EIX‐induced immune responses (Figures 7, , and ), we examined whether it affects trafficking of the PRR LeEIX2, the receptor for the family 11 xylanase EIX (Ron and Avni, 2004; Bar and Avni, 2009). We have previously demonstrated that LeEIX2 colocalizes with several early endosome/TGN markers, and is internalized on VHA1/Rab11e endosomes (e.g., Bar and Avni, 2009; Bar et al ., 2009, 2010; Sharfman et al ., 2011, 2013; Leibman‐Markus et al ., 2018; Pizarro et al ., 2019). Ligand‐dependent internalization of LeEIX2 is required for signal propagation, which occurs, in part, directly from endosomes (Ron and Avni, 2004; Bar and Avni, 2009; Sharfman et al ., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Because we determined that CK enhances EIX‐induced immune responses (Figures 7, , and ), we examined whether it affects trafficking of the PRR LeEIX2, the receptor for the family 11 xylanase EIX (Ron and Avni, 2004; Bar and Avni, 2009). We have previously demonstrated that LeEIX2 colocalizes with several early endosome/TGN markers, and is internalized on VHA1/Rab11e endosomes (e.g., Bar and Avni, 2009; Bar et al ., 2009, 2010; Sharfman et al ., 2011, 2013; Leibman‐Markus et al ., 2018; Pizarro et al ., 2019). Ligand‐dependent internalization of LeEIX2 is required for signal propagation, which occurs, in part, directly from endosomes (Ron and Avni, 2004; Bar and Avni, 2009; Sharfman et al ., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Sterols are structural components of the cell membranes and, together with sphingolipids, form the "lipid rafts" where enzyme and signaling complexes are localized 57 . Recently, sterol has been reported to be involved in induction of plant defense by T. viride 58 . In addition, sterols are precursors of the brassinosteroids, a group of plant hormones that regulate plant growth and development 57 and have the potential to increase resistance to a wide spectrum of stress in plants 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of tomato cyclopropyl isomerase (SlCPI), an enzyme involved in sterol biosynthesis, accelerates the appearance of SlEix2 endosomes, whereas silencing its N. benthamiana homolog leads to a reduction (125). Furthermore, filipin, which binds to sterols (55), negatively affects SlEix2 endocytosis.…”
Section: Subcellular Transport Of Other Pattern Recognition Receptorsmentioning
confidence: 99%